Effect of intelligence quotient discrepancy on attention and executive function in children with attention deficit hyperactivity disorder: an fNIRS study - Chen, Xin; Chen, Liang-liang; Wang, Jing-rong; Cai, Ying-ying; Yu, Xiao-dan (NeuroImage (Orlando, Fla.), 2025)
•This study represents the inaugural investigation into the neural correlates of Intelligence Quotient Discrepancy (IQD) among children diagnosed with Attention Deficit Hyperactivity Disorder (ADHD).•The activation of the right medial prefrontal cortex (RmPFC) is associated with IQD.•The IQD plays a role in both executive function and attention deficits. Intelligence quotient discrepancy (IQD) is associated with neurodevelopmental disorders, but its impact on attention and executive function (EF) deficits in children with attention deficit hyperactivity disorder (ADHD) is unknown.This study aimed to examine the effect of IQD by functional near-infrared spectroscopy (fNIRS). The current study included 114 children with ADHD and a full-scale IQ ≥ 70, encompassing verbal IQ (VIQ) and performance IQ (PIQ). Participants were divided based on IQ discrepancies into the NON-IQD (n = 60, |PIQ-VIQ| < 1 standard deviation) and IQD (n = 54, PIQ-VIQ > 1 standard deviation) groups, with 27 and 19 individuals undergoing fNIRS, respectively. Both the Behavior Rating Inventory of Executive Function (BRIEF) scale and fNIRS during a go/no-go task were utilized for the assessment of EF. Attention was measured with the Swanson, Nolan, and Pelham Version IV (SNAP-IV) scale, the Integrated Visual and Auditory Continuous Performance Test (IVA/CPT), and monitoring of 1–48 channel aberrant hemodynamics with fNIRS during the task.The study indicates that IQD plays a role in attention and EF impairment in children with ADHD, linked to abnormal hemodynamics in the right medial prefrontal cortex (RmPFC).